Adaptive Leadership in the Age of Artificial Intelligence: Language, Communication, and Cultural Transformation - Arti Tiwari; Smita Dron, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
The rapid integration of Artificial Intelligence (AI) into organizational and social systems has reshaped leadership practices, particularly in relation to language use, communication processes, and cultural engagement. This paper examines the role of adaptive leadership in managing AI-mediated communication environments characterized by technological disruption, linguistic diversity, and evolving cultural norms. Adaptive leadership enables leaders to respond flexibly to change, balance technological efficiency with human values, and foster inclusive and ethical communication. Using a conceptual and interdisciplinary approach, the study explores how AI-driven language technologies influence leadership discourse, decision-making, and organizational culture. The paper highlights the challenges and opportunities presented by AI in leadership communication and emphasizes the importance of adaptability, cultural sensitivity, and ethical responsibility in the digital era.
Keywords: Adaptive Leadership; Artificial Intelligence; Language Technology; Digital Communication; Cultural Transformation